2009
DOI: 10.1007/978-1-4419-0211-5_3
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation to the Flow Field of Venturi Injector

Abstract: Abstract:Venturi injector is widely used in fertigation system due to its obvious advantages such as cheap and robust system without mobile pieces, simple structure, convenient to operation, stable performance, needless of external energy for operation etc. At present, the hydraulic parameters such as suction capacity (injection rate) for the most of the Venturi injectors produced domestically are not very desirable. In this paper, CFD (Computational Fluid Dynamics) method was used to simulate the inner flow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Many studies have shown that throat diameter has a significant effect on the fertilizer injection performance of the Venturi injector. Huang et al (2009) and Sun et al (2012) indicated that throat diameter was positively correlated with water inlet flow and fertilizer injection amount, and similar conclusions were also drawn in this study (Figure 6c). With increased throat diameter, the fertilizer injection efficiency first increased and then decreased.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have shown that throat diameter has a significant effect on the fertilizer injection performance of the Venturi injector. Huang et al (2009) and Sun et al (2012) indicated that throat diameter was positively correlated with water inlet flow and fertilizer injection amount, and similar conclusions were also drawn in this study (Figure 6c). With increased throat diameter, the fertilizer injection efficiency first increased and then decreased.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have mainly focused on the flow inside venturi injectors. Huang et al [29,30] numerically analyzed the influence of the structural parameters on the absorption capacity. Yan et al [31] used a high-speed video camera to investigate the development of the cavitation inside a venturi injector.…”
Section: Introductionmentioning
confidence: 99%
“…It is a simple structure without mobile pieces, convenient to operate and does not require external energy for operation. 8 The injectors can be manufactured for specific size and material requirements and the suction flow rates in this experiment are controlled based on the saline flow rate. The main benefit of using this Venturi system for the application of CPB is that the suctioned blood is introduced into fluid-filled tubing, reducing the air-to-blood interface.…”
Section: Introductionmentioning
confidence: 99%